1997
DOI: 10.1007/s00050171
|View full text |Cite
|
Sign up to set email alerts
|

Induction of genes encoding plastidic phosphorylase from spinach (Spinacia oleracea L.) and potato (Solanum tuberosum L.) by exogenously supplied carbohydrates in excised leaf discs

Abstract: A full-length cDNA encoding plastidic phosphorylase (Pho1, EC 2.4.1.1) from spinach (Spinacia oleracea L.) has been isolated. Analysis of the deduced protein sequence revealed considerable homologies with the corresponding proteins from other plants, animals and prokaryotes. Escherichia coli cells carrying the entire cDNA for Pho1 expressed an active phosphorylase, which resembled the properties of the plastidic isozyme of spinach with respect to its low anity to glycogen. Expression of Pho1 was studied in spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Thus as pointed out by Duwenig et al [37] the observation that the presence of polygalacturonic acid, even though it activates bamylase for the degradation of starch, does not have any inductive effect on the activity of plastidic phosphorylase for starch degradation. Thus Duwenig et al [37] state that "… this result might be interpreted as an argument against a role of plastidic phosphorylase in starch degradation, as the gene is instead coexpressed with other genes that encode starch biosynthetic enzymes".…”
Section: Phosphorylase and The Production Of The Precursor Glycogenmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus as pointed out by Duwenig et al [37] the observation that the presence of polygalacturonic acid, even though it activates bamylase for the degradation of starch, does not have any inductive effect on the activity of plastidic phosphorylase for starch degradation. Thus Duwenig et al [37] state that "… this result might be interpreted as an argument against a role of plastidic phosphorylase in starch degradation, as the gene is instead coexpressed with other genes that encode starch biosynthetic enzymes".…”
Section: Phosphorylase and The Production Of The Precursor Glycogenmentioning
confidence: 80%
“…More recent results by Duwenig et al [37], on spinish leaves showed that the activity of the apparently single plastidic phosphorylase in spinach is increased when net starch synthesis occurs. As pointed out by Duwenig et al [37] these results, which show that the activity of phosphorylase is higher at a time when starch synthesis occurs, agree with the studies of 1) Van Berkel et al [38] who in 1991 showed that the activity of plastidic phosphorylase is higher in the developing seeds of pea cotyledones (when starch is being produced) as compared to these germinating seeds (when starch is being degraded); 2) Kossman et al [39] who in 1991 observed that plastidic phosphorylase transcript level is higher in growing potato tubers (when starch is being synthesized), as compared to that in potato sprouting tubers; and 3) Steup [40] who in 1988 showed that an increase in the activity of phosphorylase is associated, not only with starch degradation, but also with starch synthesis.…”
Section: Phosphorylase and The Production Of The Precursor Glycogenmentioning
confidence: 94%
“…cDNAs encoding the plastidic forms of SP enzymes have been isolated and characterized from a variety of higher plants (Steup, 1988). Studies with potato (Brisson et al, 1989;St-Pierre and Brisson, 1995), spinach (Duwenig et al, 1997a), and pea (van Berkel J et al, 1991) have shown that the expression of plastidic SP genes correlates with starch biosynthesis. The fact that the 112-kD SP enzyme was enriched in the amyloplast stroma where other starch synthetic enzymes are localized supports the hypothesis that SP may play some role in starch biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The insertion sequence is thought to reflect the affinity of plastidic SP enzymes for ␣-glucan substrates (Mori et al, 1993). The three peptides of the 112-kD protein also aligned closely with sequences from the plastidic SP enzymes from potato leaf (Sonnewald et al, 1995), sweet potato (Lin et al, 1991), and spinach leaf (Duwenig et al, 1997a). The N-terminal amino acid sequence of the 112-kD protein was unique and did not align with the N terminus of the plastidic SP enzymes or with any sequences in the GenBank database.…”
Section: Identification Of the 112-kd Amyloplast Stroma Protein As An Spmentioning
confidence: 91%
See 1 more Smart Citation